Quantum mechanical survey on the electronic sensitivity of aluminium phosphide monolayer toward halogen gases. Issue 5 (24th March 2023) - Kadhim, Mustafa M.; Abdullaha, Sallal A. H.; Taban, Taleeb Zedan; Alomar, T.; AI- Masoud, Nada; Hachim, Safa K.
ABSTRACT: Density functional theory computations were undertaken to scrutinise the adsorption of gasses N2, O2, F2, Cl2 and Br2 on an AlP nano-sheet (AlPNS). N2, O2, F2 and Cl2 released an adsorption energy of 3.1, 3.5, 5.3, 7.3 and 12.1 kcal/mol, respectively, as they approached the AIPNS, demonstrating a physisorption. In addition, there were no dramatic changes in the electronic properties of the AIPNS. Br2 released an adsorption energy of 23.1 kcal/mol as it approached the AIPNS. According to the electronic analysis, there was a reduction in the energy of the HOMO–LUMO gap from 2.62 to 1.76 eV (∼ −32.8%) after the adsorption of Br2, leading to a considerable rise in the electrical conductance. Hence, the AlPNS was capable of generating electrical signals as the Br2 molecules approached, which suggests that it is a promising sensor. Moreover, the AIPNS was capable of selectively detecting Br2 among the gas molecules mentioned above. The recovery time when Br2 was desorbed from the surface of the AIPNS was 6.8 s, which was short.